Reel Vulnerability : Power, Pain, and Gender in Contemporary American Film and Television - Hagelin, Sarah (Book collections on Project MUSE., 2013)
This book explores the way American popular culture thinks about vulnerability, arguing that our culture and our scholarship remain stubbornly invested in the myth of the helplessness of the female body. It examines the shifting constructions of vulnerability in the wake of the cultural upheavals of World War II, the Cold War, and 9/11, placing defenseless male bodies onscreen alongside representations of the female body in the military, in the interrogation room, and on the margins.